2005
DOI: 10.1080/09553000400017895
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lesion clustering in irradiated plasmid DNA

Abstract: In this work we have demonstrated the complex LET dependence of clustered-lesion yields, governed by interplay of the radical recombination and change in track structure. As expected, there was also a significant difference in clustered lesion yields between various radiation fields, having the same or similar LET values, but differing in nanometric track structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
72
2
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 52 publications
13
72
2
5
Order By: Relevance
“…This result could be considered to be associated with these factors, such as the type of DNA (DNA sequence), the buffer solution surrounding of DNA, radiation dose, and different LET of γ-rays used, As the frequency of DNA DSB production is so low and almost can not be detected, a slight underestimation could also be possible than the level of real ones, depending on the dose. The DSB and non-DSB cluster yields for protons radiation, in present study, show the same order as those reported by Leloup et al [19]. In Leloup's study, the pHAZE DNA irradiation was conducted in the radioquenching solution (200 mmol/L glycerol).…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…This result could be considered to be associated with these factors, such as the type of DNA (DNA sequence), the buffer solution surrounding of DNA, radiation dose, and different LET of γ-rays used, As the frequency of DNA DSB production is so low and almost can not be detected, a slight underestimation could also be possible than the level of real ones, depending on the dose. The DSB and non-DSB cluster yields for protons radiation, in present study, show the same order as those reported by Leloup et al [19]. In Leloup's study, the pHAZE DNA irradiation was conducted in the radioquenching solution (200 mmol/L glycerol).…”
Section: Resultssupporting
confidence: 74%
“…To our knowledge, although there are series of research reports regarding the efficiencies of DSBs and non-DSB clustered DNA damage induction by high or low LET radiation [7−18], very few experimental studies were conducted on the comparison of protons with heavy ions or low LET radiation. In a former report, the energy of protons and the buffer solution surrounding of DNA used is different [19], so the disaccord about yields of clustered DNA damage exist. In experiment of Leloup et al [19], pHAZE plasmid DNA was irradiated with 1.03, 19.3 and 249 MeV protons (LET=25.5, 2.7 and 0.39 keV/μm respectively) in phosphate buffer containing 2 mmol/L or 200 mmol/L glycerol, the results have shown that single-strand breaks (SSBs) yield decreased with increasing LET, the yield of DSB and all clustered lesions seemed to reach a minimum around 3 keV/μm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The unexpected results obtained by Leloup et al [13] show that the yields for SSB and DSB after irradiation with 137 Cs are higher than those obtained after irradiation with 60 Co. The authors suggest that this discrepancy can be due to differences in the spectra of the secondary electrons generated by each gamma.…”
contrasting
confidence: 37%
“…Recently, however, a work comparing the effects of gamma rays from 60 Co and from 137 Cs on plasmid DNA upon in vitro irradiation brought some doubts about the relationship between RBE and the induction of DSB lesions in the DNA molecule [13]. According to these authors, the yield for SSB and DSB induced by gamma rays from 60 Co differs from the corresponding yield induced by gamma rays from 137 Cs for equivalent delivered doses.…”
mentioning
confidence: 83%